The Mineralization Regulator ANKH Mediates Cellular Efflux of ATP, Not Pyrophosphate. (28th February 2022) - Szeri, Flora; Niaziorimi, Fatemeh; Donnelly, Sylvia; Fariha, Nishat; Tertyshnaia, Mariia; Patel, Drithi; Lundkvist, Stefan; van de Wetering, Koen
ABSTRACT: The plasma membrane protein ankylosis homologue (ANKH, mouse ortholog: Ank) prevents pathological mineralization of joints by controlling extracellular levels of the mineralization inhibitor pyrophosphate (PPi). It was long thought that ANKH acts by transporting PPi into the joints. We recently showed that when overproduced in HEK293 cells, ANKH mediates release of large amounts of nucleoside triphosphates (NTPs), predominantly ATP, into the culture medium. ATP is converted extracellularly into PPi and AMP by the ectoenzyme ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1). We could not rule out, however, that cells also release PPi directly via ANKH. We now addressed the question of whether PPi leaves cells via ANKH using HEK293 cells that completely lack ENPP1. Introduction of ANKH in these ENPP1‐deficient HEK293 cells resulted in robust cellular ATP release without the concomitant increase in extracellular PPi found in ENPP1‐proficient cells. Ank activity was previously shown to be responsible for about 75% of the PPi found in mouse bones. However, bones of Enpp1 −/− mice contained <2.5% of the PPi found in bones of wild‐type mice, showing that Enpp1 activity is also a prerequisite for Ank‐dependent PPi incorporation into the mineralized bone matrix in vivo. Hence, ATP release precedes ENPP1‐mediated PPi formation. We find that ANKH also provides about 25% of plasma PPi, whereas we have previously shown that 60% to 70% of plasma PPi is derived from the NTPs extruded by the ABC transporter, ABCC6. Both transporters that keep plasma PPi at sufficient levels to prevent pathological calcification therefore do so by extruding NTPs rather than PPi itself. © 2022 American Society for Bone and Mineral Research (ASBMR).